Pengaruh Komunikasi Interpersonal dan Kompetensi terhadap Prestasi Kerja Guru pada Sekolah Menengah Kejuruan Negeri 1 (SMKN 1) Pasir Penyu Kabupaten Indragiri Hulu - Aris Triyono; Tri Rahayu; Heriyanto Heriyanto (J-MAS (Jurnal Manajemen dan Sains), 2022)
Work performance is the result of carrying out the work achieved by an employee in carrying out the tasks assigned to him. The work performance of teachers at the Pasir Turtle State 1 Vocational High School, Indragiri Hulu Regency is suspected to have not been maximized. The purpose of the study was to analyze the effect of Interpersonal Communication and Competence on the work performance of teachers at the State Vocational High School 1 Pasir Turtle, Indragiri Hulu Regency. This type of research is quantitative. The method used to analyze the data is quantitative method, namely path analysis, correlation coefficient and determination, F test and t test. The results of Interpersonal Communication research affect teacher work performance and competence affect teacher work performance at the State Vocational High School 1 Pasir Turtle, Indragiri Hulu Regency. Optimal teacher interpersonal communication can make it easier for teachers to carry out their duties, both individual work and work that requires teamwork. Competence is a basic characteristic possessed by a person that has a direct effect on, or can predict, excellent work performance.